Developments of Pyrrolo[2,3-d]pyrimidines with Pharmaceutical Potential - Rashad, Aymn E.; El Malah, Tamer; Shamroukh, Ahmed H. (Current Organic Chemistry, 2024)
In terms of fused heterocyclic compounds, pyrrolopyrimidines, and their substituted analogs are among the most extensively explored scaffolds. Based on the location of the nitrogen atom in the pyrrole ring, pyrrolopyrimidines have different isomers. This study deals only with the pyrrolo[2,3-d]pyrimidine isomer. Several techniques are represented and discussed in this review for producing pyrrolo[2,3-d]pyrimidine derivatives. The first one is the cyclization of the pyrimidine ring on the pyrrole ring through the reaction of β-enaminonitrile, β-enaminoester or β-enaminoamide of the pyrrole ring with different bifunctional reagents such as formic acid, acetic acid, acetic anhydride, formamide, isothiocyanate, urea, thiourea, and carbon disulfide. The second technique includes cyclization of the pyrrole ring on the pyrimidine ring via the treatment of pyrimidine, aminopyrimidine, diamino-pyrimidine, or triamino-pyrimidine with different reagents such as nitroalkenes, alkynes, aldehydes, and acid chlorides. In addition, different reaction methodologies like one pot, two-step, and threestep synthetic methodologies were reported. The last technique for producing pyrrolo[2,3-d]pyrimidine derivatives is through miscellaneous reactions. This review also includes the interactions of pyrrolo[2,3- d]pyrimidines at different active centers of the pyrrole ring with different reagents to form N-alkylated, Nglycosylated, C-5, and C-6 adducts. Besides, the interactions on the pyrimidine ring to form chloro, hydrazino, and amino-imino derivatives were also discussed. The amino-imino derivatives are key intermediates for the preparation of tricyclic pyrrolotriazolopyrimidines. Finally, the pharmaceutical and biological properties of some pyrrolo[2,3-d]pyrimidine derivatives have also been mentioned. This information can be utilized to design novel diverse pyrrolopyrimidine derivatives for recent challenges in pharmaceutical and medical studies to develop the already existing drugs or discover new ones.
Keywords: biological activity